Characteristics and application of Unified Communications as a Service (UCaaS) in enterprises - Dziembek, Damian; Turek, Tomasz (Charakterystyka i zastosowanie Unified Communication as a Service (UCaaS) w przedsiębiorstwach, 2018)
The article presents the concept of unified communication in cloud computing. Nowadays communication is becoming a key management factor because of the increasing role of information resources. New concepts and models of communication are the result of the constant evolution of information technology. Multidimensional and integrated communication is an important element of modern business processes, determining their efficiency, effectiveness and performance. The first part of the study presents the basic communication tools in the organization. On this basis, the essence of Unified Communications as a Service (UCaaS) is presented as a new communication model. Next, the benefits and risks resulting from the use of UCaaS were pointed out. The last part of the article describes examples of the practical implementations of UCaaS in Polish enterprises
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 4 (50), s. 47-65
Keywords: communication; enterprise; UCaaS; komunikacja; przedsiębiorstwo